ANALISIS PERGESERAN TITIK-TITIK PANTAU TAILING DAM UTAMA (Studi Kasus PT. Aneka Tambang(Persero) Tbk. Unit Bisnis Pertambangan Emas, Pongkor) - , SANG PUTU INDRA GUNAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tailing dam serves as a residual waste of mining production.The dam should be monitored in order to determine whether there is displacement in the body of tailing dam. This activity is to minimize the possibility of accidents due to cracks, landslide or collapse. For the time being, PT Antam Tbk determine the displacement value by calculate the different coordinate measurement between one epoch to the other epoch.This method havenât applied the displacement analysis. Therefore, this research used least square adjustment method to determine the coordinate and itâs precision.The displacement analysis is performed with global congruency anddisplacement point monitoring tests. Data used in this study are horizontal angle and distance measurement of nine monitoring pointson June, July and August 2013 epoch. These monitoring points are tied to two fixed control points. Parameter method of least square adjustment computation is used to estimate the coordinate and their precisions. Then, the global statistical test is used to detect random errors. Congruency test is used to determine displacement of each points that have been monitored. Furthermore, the calculation are continued by determining the magnitude and the direction of each displacement also the displacement velocity of the monitoring points. The global test showed that there is no random error on the observation of monitoring points. The global congruency test indicated that the network configuration have been changed the shape. The single point displacement test showed that there are significant displacement at monitoring points. Theaverage velocity of displacements is 0,0780 m/month. The displacement monitoring points test showed displacement for each points that are monitored. The displacement direction of monitoring points are mostly toward the azimuth 900 untill 1800 orsoutheast towards the wasted collected.